Battery Electric Vehicle Adoption in Indonesia: Insights from Consumer Preferences and Stakeholder Perspectives - Indira Ayu Adzhani; Bambang Pramono; M. Setyawan Santoso; Mohamed Yusuf Faridian Wirayat; Liane Okdinawati; Prawira Fajarindra Belgiawan (Journal of the Civil Engineering Forum)
Indonesia’s adoption of battery electric vehicles (BEVs) remains limited, posing a challenge to the government’s ambitious targets for 2030 and beyond. This study adopts a mixed-methods approach, combining qualitative insights from focus group discussions and stakeholder interviews with quantitative analysis using a mixed multinomial logit (MMNL) model. The stated preference survey includes 1,360 respondents across six provinces in Java, providing broader geographic coverage than most prior studies in Indonesia. The analysis covers both two-wheeler (2W) and four-wheeler (4W) BEVs, while also differentiating preferences by brand, an often-overlooked factor in the Indonesian context. The MMNL results confirm that charging time, range, operational cost, and price significantly influence BEV preferences, with variations across vehicle segments and brand types. Shared concerns from both supply- and demand-side perspectives include affordability, underdeveloped charging infrastructure, and limited product-market fit. However, divergent priorities are evident: industry stakeholders emphasize the need for technological upgrades, consistent policy signals, and improvements in upstream supply chains, while consumers prioritize convenience and final purchase or operating costs, showing less sensitivity to advanced technical specifications. This study contributes to the literature by offering an integrated demand–supply perspective on BEV adoption in an emerging economy, while also introducing brand differentiation and wider geographic sampling as key novelties. Policy recommendations include accelerating fast-charging infrastructure, standardizing batteries, localizing battery production, and implementing stronger disincentives for internal combustion engine (ICE) vehicles. The strategic enforcement of Presidential Instruction No. 7/2022 is also highlighted as a critical step to demonstrate government commitment. Together, these insights provide actionable guidance for accelerating a more inclusive and effective transition to electric mobility in Indonesia.